2017
DOI: 10.1111/dme.13439
|View full text |Cite
|
Sign up to set email alerts
|

Exercise to preserve β‐cell function in recent‐onset Type 1 diabetes mellitus (EXTOD) – a randomized controlled pilot trial

Abstract: Aim Residual b-cell function is present at the time of diagnosis with Type 1 diabetes. Preserving this b-cell function reduces complications. We hypothesized that exercise preserves b-cell function in Type 1 diabetes and undertook a pilot trial to address the key uncertainties in designing a definitive trial to test this hypothesis.Methods A randomized controlled pilot trial in adults aged 16-60 years diagnosed with Type 1 diabetes within the previous 3 months was undertaken. Participants were assigned to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…This is the first study to have systematically attempted to translate the potential of exercise therapy into a behaviour change intervention for Type 1 diabetes that is suitable for implementation within a clinical setting. The study highlights the potential importance of this intervention, showing modest increases in levels of physical activity, cardiorespiratory fitness and insulin sensitivity , thus supporting the need for a longer‐term fully powered effectiveness trial. However, this study also highlights many of the same limitations that have been observed in behavioural interventions for Type 2 diabetes.…”
Section: Translating Evidence Into Practicementioning
confidence: 66%
See 2 more Smart Citations
“…This is the first study to have systematically attempted to translate the potential of exercise therapy into a behaviour change intervention for Type 1 diabetes that is suitable for implementation within a clinical setting. The study highlights the potential importance of this intervention, showing modest increases in levels of physical activity, cardiorespiratory fitness and insulin sensitivity , thus supporting the need for a longer‐term fully powered effectiveness trial. However, this study also highlights many of the same limitations that have been observed in behavioural interventions for Type 2 diabetes.…”
Section: Translating Evidence Into Practicementioning
confidence: 66%
“…The Medical Research Council framework for complex interventions provides a useful blueprint for optimizing early feasibility and pilot work in the early stages of intervention development and evaluation. In this issue of Diabetic Medicine, Narendran et al [7] follow many of the steps proposed by the Medical Research Council framework in developing and piloting a pragmatic physical activity promotion intervention for those with new-onset Type 1 diabetes. This is the first study to have systematically attempted to translate the potential of exercise therapy into a behaviour change intervention for Type 1 diabetes that is suitable for implementation within a clinical setting.…”
Section: Translating Evidence Into Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, clinical studies in individuals with type 2 DM and healthy people showed an improvement of beta‐cell function with exercise . Nonetheless, in individuals with newly diagnosed type 1 DM, a 12‐month exercise training did not result in enhanced beta‐cell function …”
Section: Discussionmentioning
confidence: 95%
“…Improved insulin sensitivity with exercise has been ª 2018 Diabetes UK demonstrated in various Type 1 diabetes populations [3]. Furthermore, recent work we have undertaken suggests that exercise improves b-cell function in Type 1 diabetes when the outcome measure is corrected for the improved insulin sensitivity that occurs with exercise [5]. Furthermore, recent work we have undertaken suggests that exercise improves b-cell function in Type 1 diabetes when the outcome measure is corrected for the improved insulin sensitivity that occurs with exercise [5].…”
mentioning
confidence: 96%